Comparison of clinical characteristics and outcomes of acute kidney injury in the elderly and younger hospitalized patients - Yesilova, A.; Toprak, I.D.; Uzun, Y.E.; Cengiz, M.; Turkmen, B.O.; Yavuzer, H.; Kocak, G. (Ukrainian Journal of Nephrology and Dialysis, 2023)
Data regarding the epidemiology, causes, and outcomes of acute kidney injury (AKI) are limited, especially in the elderly population. We aimed to investigate the clinical characteristics and early outcomes of AKI and to compare them between elderly and young patients hospitalized in an internal medicine clinic. Methods. This single-center retrospective study included patients with AKI who were hospitalized in a tertiary hospital. AKI was identified according to the Kidney Disease Improving Global Outcomes criteria. Sociodemographic, clinical, and laboratory data were recorded. Renal recovery, need for dialysis, and in-hospital mortality were compared between the elderly (>60 years) and younger (≤60 years) patients. Results. A total of 454 patients (327 elderly and 127 younger) were included in the study. The frequency of AKI in hospitalized patients was 12%. The most common cause of AKI was prerenal (61%). Prerenal AKI due to absolute intravascular volume reduction was the most important cause in both groups. Compared with the elderly patients, younger patients exhibited an increased rate of renal AKI (23% vs. 39%, p=0.001) and an increased need for dialysis during hospitalization (21% vs. 31.5% p=0.027). The incidence of vasculitis and glomerulonephritis was higher in younger patients with renal AKI than in the elderly patients (12% vs. 1.3% for vasculitis and 24% vs. 4% for glomerulonephritis p=0.001). Twenty-four percent of patients required dialysis during hospital stay and 10% required dialysis at discharge. The overall in-hospital mortality was 6,4%. Considering the AKI pathophysiology, the highest mortality rate was observed in AKI patients with renal origin (3.5%). There were no significant differences between elderly and younger patients based on renal recovery (complete recovery, 41% vs. 50%; progression 59% vs. 50%, p=0,073), hospital mortality (5.5% vs. 6.7%, p=0.634), and the need for dialysis at discharge (14% vs. 8.8%, p=0.082). Conclusions. In our study, we concluded that there was no significant difference between elderly and younger hospitalized patients according to the early outcomes of AKI. However, the younger patients had a higher rate of renal AKI with a more severe course.